Bright sinus appearance on arterial spin labeling MR imaging aids to identify cerebral venous thrombosis. Issue 41 (October 2017) - Kang, Ji Hee; Yun, Tae Jin; Yoo, Roh-Eul; Yoon, Byung-Woo; Lee, A Leum; Kang, Koung Mi; Choi, Seung Hong; Kim, Ji-Hoon; Sohn, Chul-Ho; Han, Moon Hee
Abstract : Abstract: Cerebral venous thrombosis is a potentially lethal disease. Early diagnosis is essential to improve its prognosis. However, its early diagnosis based on conventional imaging modalities remains a challenge in clinical settings. The purpose of this study was to evaluate whether bright sinus appearance on arterial spin-labeling perfusion-weighted image (ASL-PWI) could help identify cerebral venous thrombosis. ASL-PWI of 13 patients who were confirmed as cerebral venous thrombosis based on neurologic symptoms and computed tomography (CT) or magnetic resonance (MR) venography (with/without cerebral angiography) were retrospectively analyzed for the presence or absence of the following: bright signal in dural sinus termed "bright sinus appearance"; and hypoperfusion in brain parenchyma drained by thrombosed sinus. In addition, conventional MR findings, including susceptibility vessel sign, empty delta sign, and atypical distribution against arterial territory, were also analyzed. Bright sinus appearance on ASL-PWI was found in all (100%) 13 patients. In addition, 10 (77%) patients showed hypoperfusion in the brain parenchyma drained by thrombosed sinus on ASL-PWI. Susceptibility vessel sign and empty delta sign were revealed in 11 (85%) and 7 (54%) patients, respectively. Atypical distribution against arterial territory was seen in 5 (50%) of the 10 patients with parenchymal abnormality on conventional MR sequences. Therefore, the bright sinus appearance had higher sensitivities for identifying cerebral venous thrombosis than the susceptibility vessel sign, empty delta sign, and atypical distribution against arterial territory (with differences of 15%; P = .500, 46%; P = .031, and 50%; P = .031, respectively). Bright sinus appearance on ASL-PWI can provide important diagnostic clue for identifying cerebral venous thrombosis. Therefore, this technique may have the potential to be used as a noninvasive diagnostic tool to identify the cerebral venous thrombosis.